2017
DOI: 10.1177/1463949117692270
|View full text |Cite
|
Sign up to set email alerts
|

The social construction of the competent, self-governed child in documentation: Panels in the Swedish preschool

Abstract: Documentation has become an important issue for policy, practice and accountability in many national contexts. The documentation of children's activities is a requirement in the national syllabus for the Swedish preschool. However, the documentation of children is always a social construction that focuses on certain things and excludes (possible) others. Such constructions can be linked to broader discourses of the competent and self-governed child, and the tendency to label the child as autonomous and compete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
(41 reference statements)
0
13
0
4
Order By: Relevance
“…Forskare ställer också frågan om de som arbetar med pedagogisk dokumentation ger barn reella möjlighet att bli delaktiga i dokumentationsarbetet (Lenz Taguchi, 2012;Lindgren, 2012). Det finns också studier som pekar på dokumentationsmaterial som fabricerat, det vill säga att synliggörandet sker för att visa upp en god förskoleverksamhet för vårdnadshavare (Liljestrand & Hammarberg, 2017;Löfdahl, 2014).…”
Section: Inledningunclassified
See 1 more Smart Citation
“…Forskare ställer också frågan om de som arbetar med pedagogisk dokumentation ger barn reella möjlighet att bli delaktiga i dokumentationsarbetet (Lenz Taguchi, 2012;Lindgren, 2012). Det finns också studier som pekar på dokumentationsmaterial som fabricerat, det vill säga att synliggörandet sker för att visa upp en god förskoleverksamhet för vårdnadshavare (Liljestrand & Hammarberg, 2017;Löfdahl, 2014).…”
Section: Inledningunclassified
“…Dokumentationerna uppfattades inte av vårdnadshavarna som fabrikationer av den goda förskolan (Liljestrand & Hammarberg, 2017). Samtalen handlade istället om att de mindes att de hade en god inblick i verksamheten.…”
Section: Informerad Om Undervisningen -Centralt I Vårdnadshavarnas Saunclassified
“…Still, giving children a voice and stressing their own responsibility and capability might be seen as another way of controlling or governing them, since this allows only one specific way of being a child: as active, capable and responsible (Kjørholt, 2005;Söderlind & Engwall, 2005). This is also apparent in a study by Liljestrand and Hammarberg (2017), who found documentation panels, including photographs, displayed on the walls of a preschool to depict children as competent, thus excluding any other way of being a child.…”
Section: Active and Competentmentioning
confidence: 94%
“…Some focus on documentation as a means of making children's voices heard (Dahlberg, Moss, & Pence, 1999;Lenz Taguchi, 2000). Yet others focus on how visual documentation depicts children as competent, which excludes other ways of being a child (Liljestrand & Hammarberg, 2017) (cf. also Franck & Nilsen, 2015).…”
Section: The Focus Of Documentation Shifts Away From Individualsmentioning
confidence: 99%
See 1 more Smart Citation